2015
DOI: 10.1177/1524839915587269
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Quality Improvement Program for Cervical Cancer Screening at an Urban Safety Net Clinic

Abstract: This article evaluates a quality improvement program for improving guideline-consistent cervical cancer screening practices in an urban safety net clinic. Quality improvement initiatives that combine policy with practice are particularly timely in light of the alignment of cervical cancer screening guidelines released in 2012 by the most influential national organizations. A descriptive comparison design was employed using the Healthy People 2020 target of 93% screened according to guidelines. Provider-, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Another important finding from this study was that, while practitioners considered themselves as champions of self-collection, their ability to adopt a ‘ whole of practice’ approach to the implementation of the restricted self-collection cervical screening pathway remained resource dependent. Both practice champions and utilising a ‘whole of practice’ approach have been found to been characteristics of successful interventions in improving cancer screening participation within primary practice (Shaw et al., 2013 ; Hills et al., 2015 ; Weiner et al., 2017 ; Bakhai et al., 2018 ). This point is pertinent as considerations are given to how the Australia health system can foster greater adoption of self-collection cervical screening by primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Another important finding from this study was that, while practitioners considered themselves as champions of self-collection, their ability to adopt a ‘ whole of practice’ approach to the implementation of the restricted self-collection cervical screening pathway remained resource dependent. Both practice champions and utilising a ‘whole of practice’ approach have been found to been characteristics of successful interventions in improving cancer screening participation within primary practice (Shaw et al., 2013 ; Hills et al., 2015 ; Weiner et al., 2017 ; Bakhai et al., 2018 ). This point is pertinent as considerations are given to how the Australia health system can foster greater adoption of self-collection cervical screening by primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two studies from the US (n = 18), Canada (n = 3) and Australia (n = 1) were multi-component non-randomized trials (Potter et al, 2011;Kaczorowski et al, 2013;Dorrington et al, 2015;Harris et al, 2015;Hills et al, 2015;Mader et al, 2016;Marx et al, 2016;Wu et al, 2016;Baxter et al, 2017;Green et al, 2017;Hountz et al, 2017;Weiner et al, 2017;Bakhai et al, 2018;Nguyen et al, 2020;Desai et al, 2021;Funes et al, 2021;Frissora et al, 2021;Hussain et al, 2021;Jones et al, 2022;Ruggeri et al, 2020;Walker-Smith and Baldwin, 2020;Willemse et al, 2022) (Table 3).…”
Section: Multi-componentnon-randomized Trialsmentioning
confidence: 99%
“…Less common were activities on the day of an appointment, though key informants indicated that they thought huddling was likely more common than reported in studies, suggesting that some PVP practices may be routine and not described as part of an innovative practice change. Pre-visit planning practices identified in the literature mostly encompassed 2-3 16,[18][19][20][21][22]24,25,[28][29][30][31][32][33] of the AMA's 10 steps while 5 studies reported just 1 activity (though these were substantive efforts to prepare the patient for a productive visit), 15,26,[34][35][36][37] and 9 studies reported 4 or more steps, 5,17,23,27,38,[39][40][41][42] with 8 being the most steps reported in 1 article. 5 Pre-visit planning seems to be used primarily to ensure that health maintenance is up to date, current laboratory data are available, and patients have set priorities for their visit.…”
Section: Potential Solutions For Pvpmentioning
confidence: 99%
“…Both the literature and the interviews revealed a focus on a high-risk group (eg, patients with diabetes or those taking opioids), 5,23,28,30,[33][34][35][36] and/or quality metrics (eg, pneumococcal vaccination rates) as common strategies for implementing PVP. 5,[15][16][17][18][19][20][21][22][23][24] Most efforts with an evaluative element (14 of 24) described in the literature were implemented within a process improvement setting and utilized quality improvement, plan-do-study-act, or Lean methods. Such approaches seemed to be a facilitating factor for implementation as multiple improvement cycles were often utilized to develop a sustainable workflow.…”
Section: Potential Solutions For Pvpmentioning
confidence: 99%